2021
DOI: 10.1021/acsabm.1c01042
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivities of Two Vitamin B Derivatives and Their Applications in the Perpetration of Photoinduced Antibacterial Nanofibrous Membranes

Abstract: Photoactivities and photoinduced antibacterial functions of two vitamin B2 (VB2) derivatives, riboflavin (RF) and flavin mononucleotide (FMN), were investigated by computational modeling and various experimental evaluations. Under photoirradiation, the ground state of both VB2 derivatives could be excited to generate different reactive oxygen species (ROS) by undergoing different reaction paths. The formed ROS could nonselectively inactivate microorganisms. However, both RF and FMN exhibited negligible photoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Experimental results showed that mixing such supernatant with the pathogens did not induce any killing effect, implying that the release of copper cations is not the major mechanism of antimicrobial action for the CuI-coated cotton fabrics. Even though ROS generation was reported before to account for the antimicrobial property of CuI and some other materials, , we speculate that it is not the main mechanism for the CuI-coated cotton fabrics, because (i) the presence of ROS in the CuI suspension was not detected with multiple attempts using 1,3-diphenylisobenzofuran (DPBF) as the probe, (ii) the CuI-coated fabrics need much shorter contact time to inactivate pathogens, compared to that in previous examples, , and (iii) the pathogen inactivation effect can be generally observed for both metabolically active ( e.g. , bacteria, fungi) and inactive pathogens ( e.g.…”
Section: Resultsmentioning
confidence: 80%
“…Experimental results showed that mixing such supernatant with the pathogens did not induce any killing effect, implying that the release of copper cations is not the major mechanism of antimicrobial action for the CuI-coated cotton fabrics. Even though ROS generation was reported before to account for the antimicrobial property of CuI and some other materials, , we speculate that it is not the main mechanism for the CuI-coated cotton fabrics, because (i) the presence of ROS in the CuI suspension was not detected with multiple attempts using 1,3-diphenylisobenzofuran (DPBF) as the probe, (ii) the CuI-coated fabrics need much shorter contact time to inactivate pathogens, compared to that in previous examples, , and (iii) the pathogen inactivation effect can be generally observed for both metabolically active ( e.g. , bacteria, fungi) and inactive pathogens ( e.g.…”
Section: Resultsmentioning
confidence: 80%
“…To endow textiles with antibacterial properties, the functionalization of fabrics with antimicrobial agents has been widely employed . Chemical disinfectants such as quaternary ammonium compounds, N-halamines, and triclosan serve as common antimicrobial agents for constructing antibacterial fabrics, and chitosan and plant extracts as natural antibacterial agents have also been incorporated into fabrics, creating antibacterial fabrics. In addition, nanoantibacterial agents such as precious metals, metal oxides, photosensitizers, carbon dots, graphene, and guanidine have been used in antibacterial fabrics. The use of chemical disinfectants can have adverse side effects on humans and the environment. Additionally, natural antibacterial agents may exhibit instability, and the high price and limited production yields associated with metal antibacterial agents restrict their widespread use in the large-scale production of antibacterial fabrics .…”
Section: Introductionmentioning
confidence: 99%
“…Novel composite films of low-density polyethylene (LDPE) containing photosensitizing riboflavin (RF) exhibit antibacterial activity, with reductions of > 99% and 94% in Gramnegative and Gram-positive bacteria, respectively [35]. Poly (vinyl alcohol-co-ethylene) nanofibrous membranes blended with RF showed great photo-induced antibacterial activity against E. coli and L. innocua in less than 20 min of UVA irradiation [36].…”
Section: Introductionmentioning
confidence: 99%